Nanopartículas lipídicas sólidas contendo óleo de babaçu (Attalea speciosa Mart. ex Spreng.) e copaíba (Copaifera multijuga Hayne) e avaliação do seu potencial para o câncer de próstata - SILVA, Michael Jackson Ferreira da (2024)
Prostate cancer (PCa) presents many clinical, genomic and histomorphological variations, and generally grows slowly. Several processes can cause malignant transformation of prostate cells, which may begin as prostatic intraepithelial neoplasia, followed by localized PCa. Subsequently, it can progress to locally invasive adenocarcinoma, with metastasis to bones or lymph nodes, and develop an androgen independent phenotype, with a poor prognosis. Surveillance, prostatectomy, and radiotherapy are standard treatments for patients with stage I to III PCa. Androgen ablation, by surgical or pharmacological castration, is an option for high-risk stage IV and III patients. In stage IV, there is a very high probability of castration resistance, characterized by genomic mutations in the androgen receptor. Studies suggest that the combination of babassu oil (Attalea speciosa Mart. ex Spreng.) (BO) and copaiba oil-resin (Copaifera multijuga Hayne) (CO) holds promise as a phytotherapeutic alternative for prostate pathologies such as benign prostatic hyperplasia (BPH). Nonetheless, there is a lack of published research on the combined use of these oils in PCa treatment. In this study, we propose the development and characterization of solid lipid nanoparticles (SLNs) containing BO and CO, evaluating the synergistic impact on antineoplastic activity in an in vitro malignant prostate neoplasia model. Using the emulsification-ultrasonication method, we developed 19 SLNs (F1 to F19) in the initial phase, varying component and oil concentrations. SLNs underwent screening for hydrodynamic size (nm) and polydispersity index (PDI). Subsequently, F5 or SLN-BO-CO (4g stearic acid, 1g BO, 1g CO, and 2.5g Tween 80®) exhibited optimal size and PDI results (177.9 ± 1.70 and 0.245 ± 0.016, respectively), compared to F11 or SLNV (F5 without oils) (448.4 ± 9.75 and 0.238 ± 0.052) assessed 50 minutes post-formulation. To understand the influence of components on F5, 22 factorial design with a center point was employed to assess the impact of stearic acid and Tween 80 on particle hydrodynamic diameter and polydispersity index (PDI). Additionally, the effect of temperature (8 ± 0.5 ºC and 25 ± 1.0 ºC) and time (0, 7, 15, 30, 40, and 60 days) on HD and PDI values was investigated. Zeta potential (ZP) measurements were utilized to evaluate nanoparticle stability, while transmission electron microscopy provided insights into the morphology and nanometric dimensions of the SLN. Notably, before SLN synthesis, the identification and quan-tification of methyl esters, such as lauric acid and β-caryophyllene, were carried out using gas chromatography coupled to mass spectrometry (GC-MS). Moreover, the encapsulation efficiency of BBS and COPA within the SLNs was assessed. The in vitro cytotoxic activity of the SLN (10 µg/mL, 30 µg/mL, 40 µg/mL, and 80 µg/mL) was evaluated using the MTT assay with PC-3 and DU-145 prostate cancer cell lines. Results demon-strated that SLNs containing BO and CO in a 1:1 ratio exhibited a promising cytotoxic effect against prostate cancer cells, with a percentage of viable cells of 68.5% for PC-3 at a concentration of 30 µg/mL and 48% for DU-145 at a concentration of 80 µg/mL. These findings underscore the potential therapeutic applications of SLNs loaded with BO and CO for prostate cancer treat-ment.